Internal Quality Audit Optimization At University Of Sumatera Utara Using K-Nearest Neighbour - Malinda Sari Sembiring; Vicky Rosalia (Yayasan Riset dan Pengembangan Intelektual, 2023)
Internal quality audits play a pivotal role in ensuring the operational success of higher education institutions. Given the complexity and scale of activities within today's colleges and universities, conducting objective and activity-independent internal quality audits becomes essential. These audits aim to add value and enhance the organization's operations by adopting a systematic and disciplined approach to assess and improve risk management, control, and governance processes. In this research, we propose a novel approach to enhance the accuracy and efficiency of internal quality audits. The study focuses on processing internal quality audit data from auditors and the Quality Control Circle (QCC) of Magister of Accounting, utilizing a suitable k-nearest neighbor method. The generated system aims to provide alternative calculation processing for internal quality audit results, enabling auditors to obtain more representative outcomes. Additionally, the system facilitates better documentation practices, making it convenient for internal quality auditors to access and use the data effectively. The research findings demonstrate significant improvements, with the accuracy value reaching an impressive 75.00%, and an AUC value of 0.88 in the Excellent Classification group. These outcomes hold promising implications for the future work of internal quality auditors, empowering them to deliver more reliable and comprehensive audit results.